Identificación y análisis de los cuidados posturales de la enfermedad ela (esclerosis lateral amiotrofica), para el diseño de una solución ergonómica de un caso en estudio - Arias Escobar, Byron Geovanny (2016)
This research includes the design of an equipment with ergonomic features based on anthropometric measurements of the patient specifically studied, by which the researchers identified and analyzed the postural care of ALS disease (amyotrophic lateral sclerosis); while the objectives were achieved so, locomotives stages of the disease was studied and postural ergonomic chair wheels are designed based on the dimensions of the patient studied in order to improve the quality of life of both the patient and support staff family caregivers in their daily lives which they were verified by the different research tools and sheets prescription made. The enhancement of this research is the ergonomic comfort in their different daily postures that makes the person with ALS (amyotrophic lateral sclerosis)….